Analysis of the impact of metal thickness and geometric parameters on the quality factor-Q in integrated spiral inductors by means of artificial bee colony technique - Hamid Bouyghf; Bachir Benhala; Abdelhadi Raihani (Institute of Advanced Engineering and Science, 2019)
The goal of this present paper is to design, analysis the influence of the inductor geometrical parameters and the effect of the metal thickness on the quality factor-Q in integrated square spiral inductor using an efficient application of the artificial bee colony (ABC) algorithm. The inductors were optimized at 2.4 GHz to determinate their major geometrical dimensions (sp, w, din…) and their number of turns, for uses in radio-frequency integrated circuits (RFICs). The optimization results are validated by the simulation using an electromagnetic simulator (ADS-Momentum). Using matlab software, the study on the impact of the effect of geometrical parameters and the effect of metal thickness, on the factor of quality-Q of spiral inductors, is shown. We first reported that it is possible to improve Q-factors further by increasing the metal thickness, and in the design of inductor; a compromise must be reached between the value of w, n, sp and din to achieve the desired quality factor-Q and other electrical parameters.